SISTEM PAKAR DIAGNOSA PERMASALAHAN PADA PESAWAT CESSNA GRAND CARAVAN 208B MENGGUNAKAN METODE BACKWARD CHAINING - Rianto, Rianto (Sekolah Tinggi Teknologi Adisutjipto, 2016)
Success of an aircraft mechanic is to find a problem and solve it. Analysis of the problems in the Cessna Grand Caravan 208B needed someone expert in the field of aircraft mechanics. In this research expert system is used to provide easily diagnose problems with the Cessna Grand Caravan 208B by adopting the knowledge possessed from a professional mechanic, then take it into the software, that will be called by the expert system. Backward Chaining method used to obtain the results as expected by a professional mechanic. Search tecniques used to supplement the backward chaining method is a Best-First Search technique. Best-First Search Techniques is a search technique to that used to perform a search based on the knowledge gained to conduct a proper solution where it is located.